P-2 Advance care planning (ACP): The national heart centre singapore (NHCS) experience. (1st September 2015) - Lim, SM; Tan, SH; Ng, CSH; Lau, Cindy SL; Wong, Jane CQ; Tan, BC; Wong, G; Sim, KLD
Abstract : Background: NHCS Heart Failure team and Medical Social Workers (MSWs) spearheaded ACP in August 2012. The Programme now incorporates sub-clinical teams, with support from 2 Clinical Coordinators, covering: Education, Research, and Clinical. Aim: The team aims to increase awareness of ACP amongst Healthcare Workers (HCWs) in a South-East Asian (SEA) acute hospital, and to facilitate the understanding amongst MSWs of the impact of ACP on patients. ACP programme strives to ensure that patients of different disease stages and cardiac sub-specialities can benefit. Methods: The ACP programme involves educational lectures delivered by MSWs for HCWs, pre/post-test surveys with patients and collaboration with DUKE-National University of Singapore and Singapore General Hospital MSWs. NHCS specialist physicians are involved in the formulation of workflows and protocols. Results: The educational lectures enjoyed good participation (162 registered/enrolled nurses and physicians). 20 HCWs trained in facilitating the delivery of ACP. Collaboration with the aforementioned institutions produced a manuscript, a research paper and two ongoing studies. Subspecialty-specific workflows were developed after consultation with NHCS cardiologists, targeting wide range of cardiac patients. Discussion: Patients and HCWs often find it difficult to discuss the crucial issue of ACP in view of Asian sensitivities. A holistic approach towards ACP in terms of educational lectures, training, and formulation of workflows greatly assisted NHCS in establishing a platform for future studies, research and improvement to the provision of care to our patients. Conclusion: Ongoing education and advocacy of ACP to patients and healthcare stakeholders is necessary in increasing the recognition of ACP as part of standard patient care.